Avaliação dos impactos na vegetação após a exploração madeireira em floresta ombrófila densa de terra firme no Município de Caracaraí - RR - Condé, Tiago Monteiro (2011)
Changes on floristic composition and phytosociological and damage we evaluated in forest subjected to reduced-impact logging (RIL) in the municipality of Caracaraí in the state of Roraima. The experiment consisted in the installation of nine permanent plots (1 ha each), under the completely randomized design with three replications and three treatments (T1 = natural forest; T2 = forest subjected to reduced-impact logging + vine cutting; T3 = forest subjected to reduced-impact logging + cutting vines + girling). Before logging, 4.724 individuals were found, distributed in 42 botanical families, 111 genera and 165 species, and the plant families with the highest number of individuals were Fabaceae (1883), Lecythidaceae (609), Sapotaceae (434) and Arecaceae (254). The three species with the highest values of IVI, in descending order, were: Pentaclethra macroloba (52,06%), Eschweilera bracteosa (23,72%) and Pouteria caimito (8,10%). After the reduced-impact logging (RIL) with 3 trees extracted per hectare (DBH > 50 cm), corresponding to 18,66 m3/ha and application silvicultural treatments, we found no significant changes in floristic composition and phytosociological and diametric frequencies in the forest. The forest diversity and equability did not change significantly (before: Shannon = 3,27 and Pielou = 0,64; After: Shannon = 3,26 and Pielou = 0,64). Logging generated an average of 41 damaged trees / ha and 32 dead trees / ha, equivalent to 15 damaged trees per harvested tree per ha and 12 dead trees per harvested tree per ha. Most damage to remaining vegetation resulted in the formation of gaps due to the commercial extraction of forest trees, higher than the impact caused by construction of skid trails. Reductions of 5.96% and 18.90% in volume cormecial (DBH > 10 cm) in T2 and T3, respectively.